2005
DOI: 10.1111/j.1463-5224.2005.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital stationary night blindness in a Thoroughbred and a Paso Fino

Abstract: This report documents congenital stationary night blindness (CSNB) in two non-Appaloosa horse breeds (Thoroughbred and Paso Fino). History of vision impairment since birth, normal ocular structures on ophthalmic examination, and electroretinographic findings were consistent with CSNB. In one horse (Thoroughbred), a 9-year follow-up was carried out. In the Paso Fino, severe vision impairment from birth to approximately 1 year of age in both dim and bright light situations led to humane euthanasia and histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 14 publications
(52 reference statements)
1
25
0
2
Order By: Relevance
“…The a‐wave of the ERG represents the photoreceptor response to light stimulation, while the b‐wave directly relates to bipolar cell activity 23 . The dark‐adapted ERG recordings in the Miniature horse in this study were characteristic and similar to those reported previously in CSNB‐affected horses 1–6 . In this study, however, our main purpose was to confirm a diagnosis of CSNB‐affected Miniature horses rather than study the ERG characteristics with more in‐depth protocols.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The a‐wave of the ERG represents the photoreceptor response to light stimulation, while the b‐wave directly relates to bipolar cell activity 23 . The dark‐adapted ERG recordings in the Miniature horse in this study were characteristic and similar to those reported previously in CSNB‐affected horses 1–6 . In this study, however, our main purpose was to confirm a diagnosis of CSNB‐affected Miniature horses rather than study the ERG characteristics with more in‐depth protocols.…”
Section: Discussionsupporting
confidence: 69%
“…Congenital stationary night blindness (CSNB) is a nonprogressive inherited condition reported most commonly in the Appaloosa horse 1–5 . This condition has also been described in the Paso Fino and Thoroughbred breeds 6 . CSNB is characterized by impaired vision in dark conditions, and is present at birth 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in human nyctalopin ( NYX ) cause X-linked forms of CSNB [36] likely by the loss of localization of TRPM1 to depolarizing cell dendrites [37,38] and thus NYX may explain other forms of CSNB in the horse unrelated to LP [39]. TRPM1 has also been localized to the synaptic ribbons of rods and melanopsin-expressing photosensitive retinal ganglion cells [40,41] suggesting yet undiscovered roles for this gene in vision.…”
Section: Discussionmentioning
confidence: 99%
“…Affected animals characteristically show poor vision in dim light and normal vision in bright light, but a wide variation in the severity of visual deficits has been observed (Nunnery et al 2005; Witzel et al 1978). More recently clinical diagnosis of CSNB has been reported in the Danish Knabstrupper (de Linde Henriksen et al 2007).…”
Section: Simple Genetic Diseases Of the Domestic Horsementioning
confidence: 99%